Investment Incentives and Tax Competition under the Allowance for Growth and Investment (AGI) - Seppo Kari; Jussi Laitila; Olli Ropponen (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
The European Commission's Allowance for Growth and Investment (AGI) has proposed investment incentives in its two-step approach towards the Common Consolidated Corporate Tax Base (CCCTB). In this latest EconPol working paper, the authors demonstrate that the AGI strengthens investment incentives in high-tax countries and decreases the CCCTB-induced investment push towards low-tax countries. They also demonstrate that the AGI decreases tax competition and that a sufficiently generous AGI reduces tax competition between countries when introduced with the CCCTB.
Keywords: 330